Transformative Christian Education Based on Local Wisdom Mesesakaeng at Sangihe Talaud Evangelical Christian Church - Hendro Meidy Devid Dededaka; Benny B. Binilang; Yohan Brek (Peneliti.net, 2023)
This research is related to the local wisdom of mesesakaeng as the foundational bedrock for the paradigm of Transformative Christian Education. Mesesakaeng or boating is one of the local wisdoms of the people of the Sangihe, Siau, Tagulandang, and Biaro islands (hereinafter referred to as Nusa Utara). The purpose of this study was to examine and analyze the concepts and values ​​in local wisdom of mesesakaeng, the implementation of mesesakaeng in GMIST services, the obstacles and handling of mesesakaeng implementation, and the implementation of mesesakaeng-based transformative Christian education for good governance/management in the Sangihe Talaud Evangelical Christian Church (GMIST). The research method used is qualitative with an ethnographic approach. The data was collected data by employing techniques of observation, interviews, and documentation studies. Based on research data and analysis, it was found that mesesakaeng comprises the concept of Life Education, Boat Theology, and Good Governance Based on Mesesakaeng. The values ​​of perseverance, divine values, and managerial values ​​were also found as the main values ​​with various explanations. The Sangihe Talaud Evangelical Christian Church, the largest congregation is in Nusa Utara, uses a boat as the official institutional logo. However, despite the iconic representation of a boat within the institutional insignia of the Sangihe Talaud Evangelical Christian Church, the comprehensive integration of mesesakaeng's essence remains an aspiration rather than an established norm. The resonance between theoretical foundations and practical embodiment appears fragmented, with a discernible gap existing between conceptual ideals and pragmatic implementations across diverse dimensions of services. This research also contributes to an awareness campaign for GMIST congregations to make the sea as a living space and boats as means of earning a living, as well as contributing to a better pattern of stewardship of the GMIST organization (good church governance).